Semiotic Analysis on Verbal and Visual Signs in Cyber Safety Poster - Widianti, Ni Komang; Mulyawan, I Wayan; Setianingsih, Ni Ketut Alit Ida (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2024)
The title of this research is Semiotic Analysis on Verbal and Visual Signs in Cyber Safety Posters. There are two aims of this study. They were to find out the types of verbal and visual signs and describe the meaning and function of verbal and visual signs in cyber safety posters. In this study, a cyber safety poster was discussed. The poster won the golden prize in the 2013 Information Security Awareness Video & Poster Contest. The data were collected from the posters using documentative and note-taking techniques. After the data were collected, they were descriptively analysed based on the Semiotic theory proposed by Pierce (in Chandler, 2007) and the theory types of meaning and function proposed by Leech (1981). The data analysis was presented through formal and informal methods. The result of the analysis showed that verbal signs dominated the poster. Then, based on the Semiotic theory proposed by Pierce, three sign classifications were found in the data. They were 4 signs classified as Rhematic Indexical Sinsign, 2 signs were (Rhematic) Iconic Sinsign, and a sign categorised as Rhematic Symbol (ic Legisign). The result indicated that the cyber safety posters dominantly used Rhematic Indexical Sinsign, a sign based on real experience. Meanwhile, based on the theory types of meaning and function proposed by Leech (1981), the analysis showed that there were 4 conceptual and 3 connotative meanings, 4 informative and 3 directive functions. It meant that conceptual meaning and informative function were the dominant types used in the Cyber Safety poster. Keywords: Semiotics, Verbal, Visual, Sign, Poster